1988
DOI: 10.1080/10862968809547624
|View full text |Cite
|
Sign up to set email alerts
|

Does Figurative Language Present a Unique Comprehension Problem?

Abstract: In order to investigate whether or not the interpretation of figurative passages presented a comprehension problem unique to that of any difficult text, 50 undergraduate education majors were asked to read and interpret a nonliteral comparison passage and two researcher-constructed figurative passages. Subjects took pretests to measure their general vocabulary knowledge and inferencing ability. Performance on these measures was compared with abilities considered unique to the comprehension of figurative expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The qualitative analysis of the data in this study revealed a difficulty with figurative language and with implicit meanings requiring inferencing. Taking the case of figurative language alone, several reading researchers have acknowledged its role in comprehension difficulties (O'Brien & Martin, 1988). It an examination of Ortony's (1979) salience imbalance model of figurative language comprehension, Readence, Baldwin, Martin, and O'Brien (1984) hypothesized a series of steps a reader must make in order to correctly process figurative language.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative analysis of the data in this study revealed a difficulty with figurative language and with implicit meanings requiring inferencing. Taking the case of figurative language alone, several reading researchers have acknowledged its role in comprehension difficulties (O'Brien & Martin, 1988). It an examination of Ortony's (1979) salience imbalance model of figurative language comprehension, Readence, Baldwin, Martin, and O'Brien (1984) hypothesized a series of steps a reader must make in order to correctly process figurative language.…”
Section: Discussionmentioning
confidence: 99%